MODEL PEMBELAJARAN INKUIRI UNTUK MENGEMBANGKAN KREATIVITAS SISWA SEKOLAH DASAR - Elzyca Alastia Fitri (Journal of Innovative Counseling : Theory, Practice, and Research, 2017)
In the 21 century national development not only just on how to improve living standard, but also on all aspects. Therefore the necessary ability is to have intelligence and creativity, personality and life skills. Creativity is important to e developed through learning for the provision of the life by students. One of the alternative learning that can develop creativity islearning that gives space to students to be able to find and build their own concepts. The leraning model that can be applied is the inquiry learning model. This model can develop studeny creativity if supported by a student-cenered learning atsmosphere, so students are free to express ideas and also a learning environment that keeps student active in learning.